Research on E-commerce boosts the normalized assistance mechanism of rural low-income population under the background of "Internet +" - Haifang Sui; Dongsheng Liao; Chunyu Zhang (Journal of Frontier in Economic and Management Research, 2025)
China has eliminated absolute poverty.Under the new situation,the specific target of assistance for rural revitalization is the rural low-income population.Driven by "Internet plus" technology, rural e-commerce has developed rapidly and played a huge role in the development process of rural economy.In the transitional stage of consolidating and expanding the achievements made in poverty alleviation in coordination with the extensive drive for rural vitalization, e-commerce has provided a convenient way for rural low-income people to improve their lives, and has worked on infrastructure, industry and jobs,all achieved obvious results.According to the development status of rural e-commerce and rural low-income population,the author puts forward the construction ideas of normalized assistance mechanism from endogenous power, "Party building + e commerce + help" mode, brand building and other targeted assistance.